HUBUNGAN SUPERVISI KEPALA RUANGAN DENGAN KEPUASAN KERJA PERAWAT DI RSUD Dr. PIRNGADI MEDAN - Suherni Suherni (Jurnal Keperawatan Priority, 2018)
The image of the hospital is influenced by the services provided by the nurse, where the nurse is the largest employee in the hospital and the spearhead of service delivery. The indicator of hospital health service quality is nurse job satisfaction where nurse job satisfaction indirectly describes good nursing management system so that satisfaction can be formed and one to improve nurse work satisfaction is supervision given by head of room. The purpose of this study is to see the relationship of the supervision of the head of the room with the work satisfaction of the nurses. The sample in this research is 143 nurses by purposive sampling. The instruments used are the head supervision data questionnaire and the satisfaction of the nurses' job satisfaction. Test the hypothesis using spearman test rho. Based on the analysis of the data, obtained p value of 0.000 (<0.05) value r = 0.665, it show that there is a significant relationship between the supervision of the head of the room with job satisfaction nurses. The better the supervision performed, the higher the job satisfaction of the nurses. Expected for nursing practice to conduct supervision of the head of the room in order to be sustainable to maintain job satisfaction and performance of nurses implementing in accordance with the vision, mission, and goals of nursing services